2022
DOI: 10.1111/pbi.13868
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐omics profiling reveals comprehensive microbe–plant–metabolite regulation patterns for medicinal plant Glycyrrhiza uralensis Fisch

Abstract: Summary Glycyrrhiza uralensis Fisch is a medicinal plant widely used to treat multiple diseases in Europe and Asia, and its efficacy largely depends on liquiritin and glycyrrhizic acid. The regulatory pattern responsible for the difference in efficacy between wild and cultivated G. uralensis remains largely undetermined. Here, we collected roots and rhizosphere soils from wild (WT) G. uralensis as well as those farmed for 1 year (C1) and 3 years (C3), generated metabolite and transcript data for roots, microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…In the case pf medicinal plants, specific microorganisms may be directly related to the biosynthesis of medicinal components of the host plant. For example, Lysobacter was identified strongly associated with gene CYP72A154, which was required glycyrrhizic acid biosynthesis of Glycyrrhiza uralensis Fish ( Zhong et al., 2022 ). Therefore, to further elucidate the relation between differential microbial community, differential secondary metabolites and medicinal components, two interactive networks were constructed ( Figures 6 , 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the case pf medicinal plants, specific microorganisms may be directly related to the biosynthesis of medicinal components of the host plant. For example, Lysobacter was identified strongly associated with gene CYP72A154, which was required glycyrrhizic acid biosynthesis of Glycyrrhiza uralensis Fish ( Zhong et al., 2022 ). Therefore, to further elucidate the relation between differential microbial community, differential secondary metabolites and medicinal components, two interactive networks were constructed ( Figures 6 , 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…40 Single components of CHMs also undergo self-assembly. Licorice, the root and rhizome of Glycyrrhiza uralensis Fisch., is an important CHM that is commonly used to cure multiple diseases in Europe and Asia 41 and GA is the major constituent of licorice. Owing to its hydrophobic and hydrophilic moieties, GA shows self-assembly behavior in water to form nanofibers, which can be used to create functional hybrid materials, implying that the solubilizing result of licorice may be attributed to GA self-assembly behavior.…”
Section: Nanostructures Of Natural Small Molecules From Chmsmentioning
confidence: 99%
“…For example, comparing transcriptome profiles of one to four years old D. officinale stems revealed that key genes, such as CHS and FLS that are involved in flavonol synthesis, were highly expressed in the biennial samples, suggesting that the optimal harvesting period of D. officinale is 2-3 years ( Yuan et al., 2022 ). Moreover, multiple DEGs involved in liquiritin biosynthesis (e.g., UDP-glucosyltransferase (UGTs)), displayed distinct expression patterns in Glycyrrhiza uralensis farmed between 1 year and 3 years ( Zhong et al., 2022 ).…”
Section: Functional Gene Mining Of Medicinal Plant Transcriptome To C...mentioning
confidence: 99%